Kinerja Keuangan Memediasi Pengaruh Modal Intelektual dan Struktur Modal pada Nilai Perusahaan di Masa Pandemi Covid-19 - Meliani, Luh Ayu; Ariyanto, Dodik (E-Jurnal Akuntansi, 2021)
This study examines the effect of intellectual capital and capital structure on firm value with financial performance as a mediating variable. The sample was selected by purposive sampling technique. Data were analyzed using path analysis. The results of the analysis show that intellectual capital has no effect on financial performance, but has a positive effect on firm value. Capital structure has a positive effect on financial performance, but has no effect on firm value. Financial performance has a negative effect on firm value. The relationship between capital structure and firm value is successfully mediated by financial performance, however, financial performance does not mediate the relationship between intellectual capital and firm value. This research has implications for those who need information about company value in pharmaceutical sub-sector companies by considering the factors that influence it, especially during the Covid 19 pandemic. Keywords: Intellectual Capital; Capital Structure; Firm Value; Financial Performance.